(untitled) (Terr@ Plural, 2022)
A new configuration of the sugar-energy sector emerges in the current century, marked by a significant expansion inherent to the actions of the Government. Driven by this process, the Geographic Microregion (MRG) of Ituiutaba has, in the recent period, experienced a significant expansion of sugarcane production, confirmed by the insertion of four processing plants (three currently active). In this sense, the objective of this work is to evaluate the logic of the three sugar-energy plants located in the MRG of Ituiutaba, presenting their radius of action to understand the spaces activated by each of the units in the access to the raw material. This expansion of sugarcane cultivation occurred morely in areas destined for pastures (traditional for extensive cattle raising), resulting in the reconversion of these areas into sugarcane plantations in the recent period. We identified in the MRG the plants’ expansion of their theoretical radius of action to access the raw material due to the competition among the sugar-energy plants and other agribusiness agents. In this way, the sugar-energy plants activate very distant spaces to supply their crushing demand, reaching 94 km towards the Santa Vitória plant and 62 km towards the BP plant.